313 Importance of Surgical Approach and Resection Status on Outcomes of Patients with Adrenocortical Carcinoma (ACC). (28th February 2022) - Wong, W.Y.K.; Pitfield, D.; Challis, B.; Casey, R.; Kosmoliaptsis, V.
Abstract: Aim: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with overall poor prognosis. We aimed to examine the relationship between tumour resection margins (R0/R1), surgical approach (laparoscopic vs. open) and clinical outcomes in our practice. Method: We conducted a retrospective review of patients diagnosed with histology-proven ACC (01/2015–12/2020) who proceeded to surgery and were followed up at Addenbrooke's hospital (n = 24). We examined overall and progression-free survival (PFS) censored at date of death or at last follow-up. Results: Patients had a median(SD) age at presentation of 58.5(11.0), were female in 62.5%; median(SD) length of follow-up was 29(20.1) months. The tumour histology was oncocytic variant in 50% of cases. R0 resection was achieved in 16/23 cases and was associated with better PFS [median(SD): 28.5(19.3) months for R0 vs. 8(25.0) for R1] and overall survival [median(SD): 33(18.4) months for R0 vs. 29(22.6) for R1]. 15/16 and 1/7 patients with R0 and R1 resection respectively were alive at end of follow-up. R1 resection status and survival were associated with ENSAT stage (85.7% stage III-IV for R1 vs. 25.1% for R0) although tumour size was not significantly different. A greater proportion of R1 patients (57.1%) had laparoscopic surgery (3 of those had tumour size>6cm) than R0 patients (25%). Outcomes for oncocytic ACC tumours were not different. Conclusions: R0 resection is of paramount importance for ACC outcomes. Careful pre-operative work-up of indeterminate adrenal lesions to raise suspicion for ACC and consideration of open surgery for large tumours may help improve outcomes.